2008
DOI: 10.1007/s11626-008-9082-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of histone methylation in zygotic genome activation in the preimplantation mouse embryo

Abstract: Numerous previous studies demonstrated that gene expression was influenced by histone modifications. However, little information is available about the relation of histone methylation with embryonic gene expression. Here, we examine the significance of histone H3 dimethyl-lysine 4 (H3K4me2) during mouse zygotic genome activation (ZGA) by inhibiting demethylation with the specific histone H3 lysine 4 demethylase inhibitor bisguanidine 1c (1c). A 1c treatment of one-cell embryos did not significantly affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 30 publications
(30 reference statements)
0
22
0
2
Order By: Relevance
“…Furthermore, we showed that the rescue of HMGPI had no effect on Klf5 expression in Chd1-knockdown-Hmgpi-rescue embryos, suggesting that there is no direct interaction between Hmgpi and Klf5 during preimplantation development. The maintenance of pluripotency depends on OCT4 and NANOG functions during preimplantation development (Chen et al, 2009;Mitsui et al, 2003;Nichols et al, 1998;Shao et al, 2008). Pou5f1 and Nanog, both of which are ICM markers, negatively interact with Cdx2, a TE marker, and these three genes are key regulators in cell fate specification (Chen et al, 2009;Niwa et al, 2005;Ralston et al, 2010;Strumpf et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that the rescue of HMGPI had no effect on Klf5 expression in Chd1-knockdown-Hmgpi-rescue embryos, suggesting that there is no direct interaction between Hmgpi and Klf5 during preimplantation development. The maintenance of pluripotency depends on OCT4 and NANOG functions during preimplantation development (Chen et al, 2009;Mitsui et al, 2003;Nichols et al, 1998;Shao et al, 2008). Pou5f1 and Nanog, both of which are ICM markers, negatively interact with Cdx2, a TE marker, and these three genes are key regulators in cell fate specification (Chen et al, 2009;Niwa et al, 2005;Ralston et al, 2010;Strumpf et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Histone methylation, such as H3K4me2/3, is another key histone modification and is linked with active transcription (Santos-Rosa et al, 2002) and gene activation in zygotes of mice (Shao et al, 2008) and is significant for transcriptional gene reactivation after oocyte reprogramming (Murata et al, 2010). The H3K9me3 histone methylation mark is associated with transcriptional inhibition of euchromatin, repression of chromatin, and formation of heterochromatin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that the activation occurs at the 2-cell stage in the mouse [14], but transcription actually launches at the late S phase in the 1-cell embryo [15,16]. Our recent studies found that H3K4 hypermethylation results in increased expression of embryonic genes in the 2-and 4-cell stages of mouse embryos [17]. This indicates that histone methylation may be involved in embryonic gene expression.…”
mentioning
confidence: 84%